2010
DOI: 10.1021/je9008359
|View full text |Cite
|
Sign up to set email alerts
|

Solid−Liquid Phase Diagram for the System MgCl2−NH3−CH3OH at 298 K

Abstract: The ammoniated magnesium chloride compounds MgCl2·nNH3, where n is 2, 4, or 6, are potentially usable as materials for producing anhydrous magnesium chloride. The MgCl2−NH3−CH3OH system was investigated at 298 K to determine phase stability regions for hexammoniate (HEX), tetrammoniate (TET), and diammoniate (DI). Five phase regions were determined. These were: HEX+Liq, HEX+T+TLiq, T+TLiq, MgCl2·6CH3OH+T+TLiq, and a ternary liquid phase, TLiq. The phase represented by the symbol T is a previously unknown terna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The solubility of methanol and ethanol reported in the works of Lloyd et al and Pownceby et al are compared with our measured data, and the results are shown in Figure . It can be seen that the solubility in methanol measured in this work is agreed with the values reported by Lloyd et al at temperature below 310 K. However, the deviations become larger as temperatures exceed 320 K. Moreover, the solubility in methanol determined by Pownceby et al at 298 K is larger than the ones reported by us and Lloyd et al For the solubility in ethanol, the data presented in this work is in good agreement with the literature values of Lloyd et al The deviations of solubility collected from different sources may attribute to the different experimental procedure.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…The solubility of methanol and ethanol reported in the works of Lloyd et al and Pownceby et al are compared with our measured data, and the results are shown in Figure . It can be seen that the solubility in methanol measured in this work is agreed with the values reported by Lloyd et al at temperature below 310 K. However, the deviations become larger as temperatures exceed 320 K. Moreover, the solubility in methanol determined by Pownceby et al at 298 K is larger than the ones reported by us and Lloyd et al For the solubility in ethanol, the data presented in this work is in good agreement with the literature values of Lloyd et al The deviations of solubility collected from different sources may attribute to the different experimental procedure.…”
Section: Resultsmentioning
confidence: 63%
“…Therefore, it can be inferred that weak polarity of the alcohol would depress the dissolution of MgCl 2 . The solubility of methanol and ethanol reported in the works of Lloyd et al 33 and Pownceby et al 20 The log of the solubilities in single alcohol as a function of 1/ T is demonstrated in Figure 4. The relationship of the log of solubilities in methanol and ethanol and 1/T can be expressed in linear functions.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We have already linked the ineffectiveness of NaCl treatment to the high Na–Cl bond dissociation energy, but it also may be a result of its significantly low solubility in methanol (1.3 g/100 g at 40 °C), which would limit the volume of chloride delivered to the CdTe layer, and thereby account for the absence of measurable Cl in the XPS depth profiles. Indeed, CdCl 2 and MgCl 2 each have higher methanolic solubilities (3.4 g/100 g at 40 °C and 14.85 g/100 g at 20 °C, respectively) than NaCl . The observation that device efficiencies following both MgCl 2 and NH 4 Cl treatments were improved when chloride‐in‐water solutions were used (rather than chloride‐in‐methanol) lends support to the importance of the solubility of the compound, since both are particularly soluble in water (35.6 and 42.2 g/100 g, respectively) .…”
Section: Resultsmentioning
confidence: 93%
“…This is consistent with previous electrical results [ 15,17 ] showing that while for CdCl 2 , MgCl 2 , and NH 4 Cl treatments the hole density in the bulk of the CdTe is suffi ciently high and uniform (e.g., 10 15 cm −3 for MgCl 2 ), following NaCl treatment, the hole density is low and nonuniform (10 14 cm −3 ). [ 61 ] The observation that device effi ciencies following both MgCl 2 and NH 4 Cl treatments were improved when chloride-in-water Adv. Indeed, CdCl 2 and MgCl 2 each have higher methanolic solubilities (3.4 g/100 g at 40 °C and 14.85 g/100 g at 20 °C, respectively) than NaCl.…”
Section: Chemical Analysis Of Cdte Surface and Device Stackmentioning
confidence: 99%